The Effect of Non-Physical Work Environment, nd Extrinsic Motivation On Performance Through Job Satisfaction, and Attendance as an Intervening Variable at the Santo Thomas Catholic University Medan - Yohana Mutiara; Ritha F Dalimunte; R. Hamdani Harahap (Indonesian Journal of Business Analytics, 2025)
This research originates from the necessity to explore various factors that affect the performance of educational personnel, with a specific focus on the Catholic University of Saint Thomas. Despite the influence of the physical work environment, other factors—namely the non-physical work environment, extrinsic motivation, job satisfaction, as well as attendance—play a significant role in shaping employee performance. This study uses a quantitative approach by applying a saturation sampling technique, where all members of the population are made into a research sample. Thus, a total of 91 educational personnel were involved as respondents. Data collection is done through questionnaires, interviews, as well as document analysis. The data obtained is then analyzed using SmartPLS 3 software, with path analysis as the main analysis technique. The results of this study show that the non-physical work environment has a positive as well as significant impact on the performance, attendance, as well as job satisfaction of educational personnel. In addition, extrinsic motivation is proven to have a positive as well as significant impact on employee performance as well as job satisfaction. This study also reveals that job satisfaction has a positive as well as significant impact on the attendance of work as well as the performance of educational personnel. Furthermore, employee attendance plays a role as a mediation variable in the relationship between job satisfaction as well as performance, while job satisfaction acts as a mediator in the relationship between extrinsic motivation as well as the performance of educational personnel.